## Solve using elimination. 2x – y = 0 3x – 2y = -3 Question 1 options: (5, 10)

Question

Solve using elimination.

2x – y = 0

3x – 2y = -3

Question 1 options:

(5, 10)

(-3,6)

(3,6)

(5,9)

in progress 0
3 years 2021-07-27T22:17:14+00:00 1 Answers 25 views 0

x=3,y=6

Step-by-step explanation:

2x−y=0

3x−2y=−3

​In order to solve by elimination, coefficients of one of the variables must be the same in both equations so that the variable will cancel out when one equation is subtracted from the other.

2x−y=0,3x−2y=−3

To make 2x and 3x equal, multiply all terms on each side of the first equation by 3 and all terms on each side of the second by 2.

3×2x+3(−1)y=0,2×3x+2(−2)y=2(−3)

Simplify.

6x−3y=0,6x−4y=−6

Subtract 6x−4y=−6 from 6x−3y=0 by subtracting like terms on each side of the equal sign.

6x−6x−3y+4y=6

Add 6x to −6x. Terms 6x and −6x cancel out, leaving an equation with only one variable that can be solved.

−3y+4y=6

y=6

Substitute 6 for y in 3x−2y=−3. Because the resulting equation contains only one variable, you can solve for x directly.

3x−2×6=−3

Multiply −2 times 6.

3x−12=−3

Add 12 to both sides of the equation.

3x=9

Divide both sides by 3.

x=3

The system is now solved.

x=3,y=6